Uranium isotope variation within vein-type uranium ore deposits. (August 2021) - Keatley, Anya C.; Dunne, James A.; Martin, Tomas L.; Nita, Dan C.; Andersen, Morten B.; Scott, Thomas B.; Richards, David A.; Awbery, Roy P.
Abstract: Isotopic composition of uranium has previously been used to infer the depositional redox environment of uranium ore concentrates and also provide a potential signature to inform nuclear forensic investigations. This study evaluates the diagnostic power of the U isotope signature by investigating (1) the heterogeneity of U isotope compositions in samples collected from the same mine and/or vein, and (2) the influence of U ore processing on 238 U/ 235 U and 234 U/ 238 U ratios. These characteristics are explored via high precision mass spectrometric measurement of vein type uranium ore samples collected predominantly from mines located in central Portugal and Southwest England. Samples collected from the same vein and mine exhibit δ 238 U values from −0.16 to +0.03 (±0.04) ‰ and −1.6 to −64.7 (±0.4) ‰ for δ 234 U (±2SD). These variations can be attributed to redox-driven isotope fractionation processes and/or U redistribution during localised leaching and re-precipitation. Analyses of residues and leachates from small-scale batch experiments designed to simulate industrial U ore leaching procedures reveal significant positive and negative changes in isotope composition in the leachate relative to the bulk material (up to 0.21 ± 0.06‰ for δ 238 U and 62.0 ± 0.6‰ for δ 234 U). These findings highlight the possibility of significantly different δ 238 U and δ 234 U of uranium ore concentrate from the same mine even if manufacturing processes remain unchanged. Highlights: Localised U isotope heterogeneity is observed in vein type uranium ore deposits. Changes in 234 U/ 238 U and 238 U/ 235 U are observed during acid leaching experiments. These data suggest U isotope ratios change during conversion from ore to UOC. Implications for the use of the uranium isotopic signature in nuclear forensics.